Measuring Contagion of Subprime Crisis Based on MVMQ-CAViaR Method - Wuyi Ye; Kebing Luo; Shaofu Du (Discrete Dynamics in Nature and Society)
The analysis of financial contagion is a topical issue in international finance and portfolio management. In this paper, we investigate whether the global financial crisis originating from American subprime crisis spreads to China, Japan, UK, France, and Germany. Firstly, multivariate conditional autoregressive value at risk (MV-CAViaR) models are applied to the whole sample to analyze the variation of market risk among these countries. By dividing the sampling period into three important subperiods (precrisis period, crisis period, and recovery period), we examine the changes of the dependence structure of risk during each period. Comparing with the situations in precrisis period, if the estimated coefficients become significant or market risk increases during the crisis, it implies the existence of contagion from the angle of coefficient significance or risk. The findings show that the concerned coefficients are significant or the market risks of the tested countries increase during the crisis except for China. The results imply that there is contagion from the US to all other countries, except for China. Furthermore, the changes of the market risk are found to be consistent with market events and media reports during that period.